2014 49th International Universities Power Engineering Conference (UPEC) 2014
DOI: 10.1109/upec.2014.6934721
|View full text |Cite
|
Sign up to set email alerts
|

Performance and EMC analysis of an interleaved PFC boost converter topology

Abstract: An extensive experimental analysis of a two-phase Interleaved PFC Boost converter (I-PFC-B) is presented in this paper. It aims to highlight the most important features of I-PFC-B operation, in terms of both performances and Electromagnetic Compatibility (EMC) issues. Therefore, several experimental tests are performed inside an anechoic RF chamber; in particular, Power Factor, Total Harmonic Distortion Factor, Current Crest Factor and energy efficiency are determined at different I-PFC-B output powers. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…However, despite the advantages, strengths, and promising findings of the proposed WSN architecture, it must be pointed out that the design and results are at a preliminary stage. Hence, one major limitation is that the automotive certification for the Raspberry Pi unit is not available at the moment, but some recent literature findings encourage the possibility to easily obtain it [19,23,46]. Furthermore, even though it has been demonstrated that the temperature, humidity, and bus vibrations do not affect the management of multimedia content, the data transmission in upload and download should be optimized and enhanced to avoid instabilities, since this is a primary requirement for the case company.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite the advantages, strengths, and promising findings of the proposed WSN architecture, it must be pointed out that the design and results are at a preliminary stage. Hence, one major limitation is that the automotive certification for the Raspberry Pi unit is not available at the moment, but some recent literature findings encourage the possibility to easily obtain it [19,23,46]. Furthermore, even though it has been demonstrated that the temperature, humidity, and bus vibrations do not affect the management of multimedia content, the data transmission in upload and download should be optimized and enhanced to avoid instabilities, since this is a primary requirement for the case company.…”
Section: Discussionmentioning
confidence: 99%